System of quality indicators to evaluate online postgraduate programs in Perú, 2020 (SCIÉNDO INGENIUM, 2022)
The rapid evolution of e-learning makes necessary for models to evaluate their quality to evolve in the same way, so research in this field must be constant, contributing to improve the perspective of society regarding the quality of e-learning. There is a growing number of virtual universities. On this point, some theses have been developed that show the different models of evaluation of the quality of both face-to-face education and virtual education, but not applied to the Peruvian reality and to postgraduate programs. The present qualitative research develops a system of quality indicators from comparing twenty one (21) quality models from different regions that exist to evaluate virtual programs in different regions: Latin America, Europe, Africa, USA, and that have been proposed or updated in the last 15 years, most of them between 2008 and 2011. This proposal has been validated through surveys of experts of virtual programs. In conclusion it can be indicated that fifteen (15) dimensions or factors have been identified and fifty-six (56) indicators that better allow to evaluate the quality of the graduate programs in virtual modality in Peru.
Keywords: Posgraduate; Indicators; Quality; E-Learning